(untitled) (Trabalho & Educação, 2016)
This article contributes to the debate on the relationship between the nature and dynamics of economic growth based on information-knowledge, ICTs, and the organization of poietic work in the context of contemporary peripheral informational capitalism. It reflects in particular on the nexus between labor suffering and business strategies of subjectivation based on an experience of private university teaching in Argentina (2014-2015). What are its "gender" implications in the context of the advancement of neo-classical thinking and practices during the last decades in socioeconomic, political and ideological terms? ___ Este artículo contribuye al debate sobre la relación entre la naturaleza y dinámica del crecimiento económico en base a la información-conocimiento, TICs, y la organización del trabajo poiético en el contexto del capitalismo informacional periférico contemporáneo. Reflexiona en particular sobre el nexo entre el sufrimiento laboral y las estrategias empresariales de subjetivación en base a una experiencia de docencia universitaria privada en la Argentina (2014-2015). ¿Cuáles son sus implicaciones “generizadas” en el marco del avance del pensamiento y prácticas neo-clásicas durante las últimas décadas en materia socioeconómica, política e ideológica?